Elaboración de material didáctico para el proceso de lecto-escritura, aplicando el método global en el área de lengua y literatura, en los estudiantes del Centro de Educación Básica Intercultural Bilingüe Monseñor “Lorenzo Voltini-Uruguay” Palopo-Ignacio Flores – Latacunga - Cotopaxi, periodo 2015-2016 - Negrete Yugcha, Manuel Segundo (2016)
This researching was conducted with appropriate methods and following to the structure provided by the institution, it permits to analyze the theoretical and conceptual foundation on the application of the global method in the process of education learning in the children, of the Second Year of Basic Education of the educational Intercultural Bilingual Center Monsignor “Lorenzo Voltolini Uruguay”. As they advance the years the educational formation it must acquire new methodologies, to investigate skills, which will facilitate the process of education learning and this way it will be possible improve in the area of language and the literature….